The distinguishing factor of migration in homelessness - Navarro Lashayas, Miguel Ángel (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
In recent years has increased the number of homeless immigrants. The article shows the relationship between legal status and acculturative stress with sociodemographic variables, social support, substance abuse, stressful life events and emotional distress in a sample of 107 homeless migrants. To this end has been made In-depth interviews and self-reports analyzing relationships between variables using various techniques of data analysis and content analysis. The results show the importance of the qualitative variable for «legal status» that has little correlation with the other variables. It also highlights the importance of social resources in acculturative stress over other variables such as culture shock or nostalgia for the country.